2005
DOI: 10.1007/s10495-005-1191-x
|View full text |Cite
|
Sign up to set email alerts
|

Humanin delays apoptosis in K562 cells by downregulation of P38 MAP kinase

Abstract: Humanin (HN) is a newly identified neuroprotective peptide. In this study, we investigated its antiapoptotic effect and the potential mechanisms in K562 cells. Upon serum deprivation, expression of HN in K562 cells decreased and its intracellular distribution changed from cytoplasm to cell membrane. In HN stably transfected K562 cells, apoptosis was delayed compared with control vector transfected cells as measured by flow cytometry. Furthermore, analysis of different mitogen-activated protein (MAP) kinases ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 34 publications
0
27
1
3
Order By: Relevance
“…It has been reported that the neuroprotective effect of humanin against cerebral ischemia/reperfusion injury is mediated by inhibiting ERK activation [42]. Studies have also shown that humanin could protect cultured mouse primary cortical neurons from OGD-induced injury via the PI3K/Akt pathway [43], suppress apoptosis induced by ischemia/reperfusion or other factors by downregulating p38 MAP kinase [40] and interfere with Bax activation [12,22,35], and prolong the survival of serumdeprived human lymphocytes by increasing the metabolic activity of individual lymphocytes [23]. Studies on the mechanisms involved in the neuroprotective effect of humanin against AD-related neurotoxicities have demonstrated that the binding with a novel IL-6-receptor-related receptor(s) involving CNTFRalpha, WSX-1 and gp130 on the cell surface [16,17,28] and the activation of the JAK2/ STAT3 signaling axis [5] are associated with the neuroprotective effect of humanin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the neuroprotective effect of humanin against cerebral ischemia/reperfusion injury is mediated by inhibiting ERK activation [42]. Studies have also shown that humanin could protect cultured mouse primary cortical neurons from OGD-induced injury via the PI3K/Akt pathway [43], suppress apoptosis induced by ischemia/reperfusion or other factors by downregulating p38 MAP kinase [40] and interfere with Bax activation [12,22,35], and prolong the survival of serumdeprived human lymphocytes by increasing the metabolic activity of individual lymphocytes [23]. Studies on the mechanisms involved in the neuroprotective effect of humanin against AD-related neurotoxicities have demonstrated that the binding with a novel IL-6-receptor-related receptor(s) involving CNTFRalpha, WSX-1 and gp130 on the cell surface [16,17,28] and the activation of the JAK2/ STAT3 signaling axis [5] are associated with the neuroprotective effect of humanin.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroprotective effect of humanin against cerebral ischemia/reperfusion (I/R) injury in mice has been reported to be mediated at least in part by inhibiting ERK activation [42] and the PI3K/Akt pathway [43]. Humanin could suppress apoptosis, induced by ischemia/reperfusion or other factors, by down-regulating p38 MAP kinase [40,41] and interfering with Bax activation [12,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that treatment with GA resulted in down-regulation of BCL-2, which suggested GA might induce cell apoptosis through suppressing mitochondrial pathways. Traditional clinicopathologic factors and several interesting molecules, including phosphatidylinositol 3-kinase (PI3K) [24], oncogenes such as c-myc [25], and nuclear factor-kappa B (NF-κB) have been reported to correlate to the prognosis of leukemia patients. Previous studies have also revealed numerous cellular proteins (e.g., c-myc, PI3K and AKT) were targeted by GA in several cell lines [2,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…ERK and PI3K-Akt pathways are implicated in neuroprotection of HN against cerebral ischemia/reperfusion injury in vivo [25], [26]. p38 and STAT3 are involved in apoptosis induced by trophic factor withdrawal in human leukemia cell line and pancreatic beta-cell line, respectively [28], [70]. In this study, we did not detect significant changes in phosphorylation of Tyr705 in STAT3 and Ser473 in Akt, while phosphorylation of Thr308 in Akt was significantly increased in S14G-HN-treaed 3xTg-AD mouse brains compared with control (Fig.…”
Section: Discussionmentioning
confidence: 99%